Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1098/rspb.2013.0101
|View full text |Cite
|
Sign up to set email alerts
|

Major urinary protein 5, a scent communication protein, is regulated by dietary restriction and subsequent re-feeding in mice

Abstract: Major urinary proteins (Mups) are important for rodent scent communication and sexual behaviour. Recent evidence suggests that Mup1 may be regulated by fasting and re-feeding (RF). However, other Mup isoforms are poorly investigated, and data on the impact of long-term dietary restriction (DR) and ad libitum RF on Mup expression are missing. We investigated the effects of long-term 25 per cent DR and subsequent RF on Mup expression in male C57BL6 mice. DR significantly decreased Mup gene expression, hepatic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
34
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 59 publications
5
34
1
Order By: Relevance
“…Third, we attempted to explain the disparity between gel-based and gel-free proteomic methods, and unexpectedly we found that gel-based methods do not separate MUP proteins. Our findings indicate the electrophoretic methods used for studying MUPs for the past 80 years215 – to infer similarity2, diversity111315 and other variations in MUPs3036, including hormonal regulation3738 and epigenetic control39, need to be re-evaluated. Gel-based methods provided the basis for the barcode hypothesis and claims that MUPs are highly polymorphic24 – and therefore, the hypothesis that MUPs mediate individual odour and genetic kin recognition (inbreeding avoidance)234613 also needs to be re-evaluated.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Third, we attempted to explain the disparity between gel-based and gel-free proteomic methods, and unexpectedly we found that gel-based methods do not separate MUP proteins. Our findings indicate the electrophoretic methods used for studying MUPs for the past 80 years215 – to infer similarity2, diversity111315 and other variations in MUPs3036, including hormonal regulation3738 and epigenetic control39, need to be re-evaluated. Gel-based methods provided the basis for the barcode hypothesis and claims that MUPs are highly polymorphic24 – and therefore, the hypothesis that MUPs mediate individual odour and genetic kin recognition (inbreeding avoidance)234613 also needs to be re-evaluated.…”
Section: Discussionmentioning
confidence: 94%
“…However, further analyses are needed to confirm protein identification, evaluate variation and consistency across all Mup loci, and over a longer time and across different conditions. MUP production is dynamically regulated with changes in age27, health2829, diet30, and social status3132, and we recently found that MUP proteins are differentially regulated when males are placed in competitive social conditions33. Thus, MUP expression profiles are phenotypically plastic, rather than constitutive (developmentally fixed), and studies are needed to investigate how variation and consistency in MUP expression influences individual odor , especially under more natural conditions.…”
Section: Discussionmentioning
confidence: 99%
“…56 In the present study, hepatic Mup expression was significantly reduced in dietaryrestricted mice comparable to restricted mice on a LFD. 12 …”
Section: Discussionmentioning
confidence: 99%
“…This is in line with recent findings in adult mice showing that DR reduces the number of senescent cells in tissues, including the liver, together with improved telomere maintenance but without actually increasing telomerase activity. 55 It is assumed that DR-induced life-span extension is based on an interplay between nutrition and reproduction 12 and there is evidence linking steroid signaling to nutrient-sensing pathways involving TOR. 56 In the present study, hepatic Mup expression was significantly reduced in dietaryrestricted mice comparable to restricted mice on a LFD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation